Trigger, pathogen, or bystander: the complex nexus linking Epstein–Barr virus and multiple sclerosis - Owens, Gregory P (Mult Scler, 2012)
A causal role for virus infection in the pathophysiology of multiple sclerosis (MS) has been suggested and widely debated since the landmark epidemiologic studies of Kurtzke revealed a strong environmental determinant to MS susceptibility. Despite multiple efforts, no virus has been unequivocally associated with lesion formation in the brain either by direct isolation or by indirect methods of detection. In many infectious diseases of the central nervous system, oligoclonal IgG bands are the product of a robust and specific humoral response against the causative agent; yet in MS, immunoreactivity to a primary target has been elusive. In the absence of any infectious agent fulfilling Koch’s Postulates, new concepts that could plausibly explain the epidemiology of MS have been postulated. The initiation or activation of a nascent autoimmune response in genetically susceptible individuals following exposure to one or more common infectious agents is now a leading hypothesis to explain MS pathogenesis. Epstein–Barr Virus (EBV), a human herpes virus that infects B cells in ~95% of the human population and persists latently in the memory B cell pool throughout life, has received the most attention as a probable candidate; EBV has been implicated as both an environmental trigger and as a direct causative agent of CNS immunopathology. In this review, we will discuss the most salient features of EBV epidemiology, the immunological response to EBV in MS patients and whether EBV infection of the brain is a necessary prerequisite of MS pathology.